Beliefs in Conflict: The Management of Teno Atlantic Salmon in the Sámi Homeland in Finland - Hiedanpää, Juha; Saijets, Joni; Jounela, Pekka; Jokinen, Mikko; Sarkki, Simo (Environmental Management, 2020)
Abstract The subarctic Teno River is one of the most significant spawning rivers for Atlantic salmon in Europe. In 2009, research indicated that the Teno salmon stock was in a weak state, and concern about the future of Atlantic salmon in the Teno River arose on both sides of the river, in Finland and Norway. In 2017, the governments ratified the new Teno fishing agreement (Teno Fishing Act 2017). The agreement aimed to reduce the fishing volume by 30%, and the new regulations concerned all users, including the indigenous Sámi, other locals, tourists, and fishing entrepreneurs. This triggered concern and anger in the Sámi community and among other locals generally. The dispute raised a question concerning the management of Teno salmon. We conducted a Q inquiry with 43 statements, covering aspects of interest, knowledge, management, and policy needs related to Teno salmon. We hypothesised that the key reason for the management tensions lay in how scientific and traditional knowledge fitted administrative knowledge requirements. By using self-organising maps (SOMs), four webs of beliefs emerged from the data: traditional Sámi fishing; salmon protection; equal economic opportunity; and evidence-based decision-making. We also further analysed the statements according to how they reproduced diverging and similar beliefs. We discuss the identity-related struggle, rights, and stakes and the underlying issue of confidence and respect.